Forming a social media marketing strategy: Increasing product awareness and generating leads for a startup company in diving industry - Collin, Niklas (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
Social media is used by billions of people daily to share and interact. While the main focus for many social media channels is to allow communications between individuals, companies have also noticed the vast potential social media channels have to offer. At present, many companies of varying sizes are using social media for numerous purposes, brand building, customer service and information gathering being some of the most typical. This study analyzes how social media marketing can be used to effectively promote a startup company and their product with the goal of presenting a social media marketing plan for UWIS Oy (Underwater Information Systems). UWIS is a startup company founded in Finland in 2014. They are launching a new product to completely new market within diving industry during the year 2017. Because of limited resources, UWIS has decided to use selected social media channels to raise product awareness, establish company image, manage customer relationships and gain information about the industry. In order for UWIS to achieve these goals effectively, this study examined some prominent and successful industry organizations for benchmarking purposes. A semi structured interview was conducted either via Skype or email. The interview analyzed the social media behavior of potential customers within diving industry as well as their favored content in the social media channels they use. The interviews and benchmarks derived from diving industry organizations and their activities suggest that potential customers for UWIS are people who enjoy content concerning marine life, environment and the lifestyle of diving. They prefer personal, relevant and interesting social media material that promotes the values they have and overlook promotional and impersonal messaging. The findings from benchmarks and interviews were then compared with background research and non-academic literature on social media marketing to form social media marketing plan comprising of several different important aspects that together form the social media marketing plan. The research results would indicate that the ways of effectively marketing on social media haven’t changed in the recent decade. The literature still forms a robust framework for companies to structure their social media marketing strategy on, but companies need to study their audience and potential customers in order to be able to create relevant and interesting content for them.